Perkembangan Keseimbangan pada Anak Usia 7 s/d 12 Tahun Ditinjau dari Jenis Kelamin - Widya Permana, Dhias Fajar (Media Ilmu Keolahragaan Indonesia, 2013)
Background of this static balance research and dynamic is to investigatethe development ofstatic and dynamic balancein older childrenages 7to12 years in Demak regency. The purposeof this study was to determinethe importance ofthe development of static and dynamic balance in young men and the humiliation of women aged 7-12 years inDemak regency.The method was used by the researchersin examine this research is by methods development Cross-sectional study (study the developmentalcross-sectional study ofbalance). The initial phaseis to collect student data Elementary School (SD) according to the sampling technique used,in whole school elementary school (SD) as Demak regency. The data are the names of students who will perform tests of static balance and dynamic balance. In the second stage, after the data has been collected the students performa static balance test using the tes stroke stand ÃÂ and for dynamic balance test using the floor patern The third phase was after the measurement of static balance and dynamic balance is complete, it can be presente tables and graphs, according to the data of each measurement and the balance and then compared the development of static and dynamic balanceper-ages 7 s/d12 years also gender. The next stage is to compare the development of static balance and dynamic balance between big kids boys and girls ages 7s/d12 years